Dejan Rebernik: Urbana geografija. Geografske značilnosti mest in urbanizacije v svetu. - Drozg Vladimir (Journal for Geography, 2007)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="02b2639f-1a5b-4563-be6a-3ee4ad23561b"> The book consists of an introduction and 16 chapters, followed by three lists of literature, pictures, and photographs. After the introduction, the second chapter outlines the content of urban geography and conceptual directions that have been reflected in the understanding of urban areas. The third chapter discusses the formation and development of cities, with the author focusing only on European cities. The next two chapters are dedicated to urbanization, and the sixth chapter discusses urban systems. This is followed by a chapter on the urban region. The eighth chapter, titled "Urban Structure," presents theories and models that explain it. The next three chapters cover the morphological, sociogeographic, and functional structure of the city. This is followed by two chapters on economic activities, namely industry and services, and a chapter on urban transport. The fifteenth chapter discusses degraded urban areas and urban renewal, the next one about the socialist city. The final chapter addresses cities and urbanization in the third world.